Cultural Hybridity in Focus: Exploring Globalized Identities Through Jhumpa Lahiri’s The Namesake and Alejandro González Iñárritu’s Babel - K Anil, Arjun (International Journal of Environment, Agriculture and Biotechnology, 2023)
This research paper focuses on the phenomenon of Cultural Hybridity within the realm of literature and film, honing in on specific works as case studies to illuminate the intricacies of cultural fusion in globalized societies. The chosen literary work here is Jhumpa Lahiri’s The Namesake, while the film Babel directed by Alejandro González Iñárritu serves as a cinematic counterpart. Through a meticulous analysis of these culturally rich narratives, the study explores how the characters navigate their identities in the face of globalization. The paper traverse into the ways in which the authors and filmmakers employ narrative techniques, character development, and symbolic elements to depict the hybridization of cultures. It examines how these artistic creations serve as mirrors reflecting the broader issues of diaspora, immigration, and the clash of traditional and modern values. By dissecting the chosen literary and cinematic works, this research aims to unveil the unique ways in which Cultural Hybridity is portrayed and its implications on individual and collective identity. The formal analysis of The Namesake and Babel provides a lens through which scholars and enthusiasts can deepen their understanding of how cultural amalgamation is articulated in creative expressions, enriching the discourse on the intersection of art, culture, and globalization.